Kepatuhan wajib pajak PBB di Desa Tawengan: Dampak pemahaman pajak, sanksi dan kepercayaan pada pemerintah - Melvi Indy Anggawati; Heni Susilowati (Journal of Accounting and Digital Finance, 2025)
Taxpayer compliance is a key indicator of tax collection effectiveness, including Land and Building Tax (PBB), an important source of local revenue. This study examines the effects of tax knowledge, tax sanctions, and trust in government on PBB taxpayer compliance. The study population consisted of registered taxpayers in Tawengan Village, Boyolali. A quantitative survey design was employed, with questionnaires distributed to 100 respondents, and the data were analyzed using multiple linear regression. The findings indicate that, in part, understanding of tax regulation and tax sanctions does not have a significant effect on taxpayer compliance. However, trust in government has a positive and significant impact on taxpayer compliance. Simultaneously, understanding of tax regulations, tax sanctions, and trust in government significantly influence PBB taxpayer compliance. These results imply that village governments and tax officers should prioritize building public trust through educational approaches and policy transparency, rather than relying primarily on deterrence through administrative sanctions.